(untitled) (Colombia Medica, 1988)
With the recent implementation of the government-opposition political scheme, Colombia is living in a new era in which significant elements of an open and participatory democracy prevail. This political model is intended to provide a broad framework for developing a democratic debate in which political options and alternatives are openly debated.